2016
DOI: 10.1038/ejhg.2016.182
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic yield of whole-exome sequencing targeting a gene panel for hearing impairment in The Netherlands

Abstract: Hearing impairment (HI) is genetically heterogeneous which hampers genetic counseling and molecular diagnosis. Testing of several single HI-related genes is laborious and expensive. In this study, we evaluate the diagnostic utility of whole-exome sequencing (WES) targeting a panel of HI-related genes. Two hundred index patients, mostly of Dutch origin, with presumed hereditary HI underwent WES followed by targeted analysis of an HI gene panel of 120 genes. We found causative variants underlying the HI in 67 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 40 publications
7
60
2
Order By: Relevance
“…Currently, the most cost-effective approach is using comprehensive panels of genes involved in inherited HI, which can provide sequencing data as well as detection of copy number variants (Shearer and Smith, 2015 ). Other laboratories use whole-exome sequencing followed by targeted analysis of genes known to be involved in HI (Zazo-Seco et al, 2017 ).…”
Section: Genetic Alterations That Results In Dfnb1 Hearing Impairmentmentioning
confidence: 99%
“…Currently, the most cost-effective approach is using comprehensive panels of genes involved in inherited HI, which can provide sequencing data as well as detection of copy number variants (Shearer and Smith, 2015 ). Other laboratories use whole-exome sequencing followed by targeted analysis of genes known to be involved in HI (Zazo-Seco et al, 2017 ).…”
Section: Genetic Alterations That Results In Dfnb1 Hearing Impairmentmentioning
confidence: 99%
“…Therefore, MYO6 is considered an important causative gene for Japanese patients with ADSNHL. However, this is not a population-specific phenomenon as Seco et al recently also reported that the MYO6 gene is a frequent cause of AD hearing loss in the population in the Netherlands [30].…”
Section: Discussionmentioning
confidence: 91%
“…Approximately 70% of affected individuals have nonsyndromic hearing loss (NSHL), which currently has over 115 recessive, dominant and/or X-linked genes implicated in its molecular pathogenesis (https :// hered itary heari ngloss.org/). The DFNB1 locus (GJB2 and GJB6) accounts for ~50% of severe to profound congenital NSHL cases, followed by USH2A, STRC, and MYO15A (Francey et al, 2012;Vona et al, 2015;Zazo Seco et al, 2016). Pathogenic recessive sequence variants in STRC were first reported in 2001 and this gene is now estimated to account for ~5%-6% of all congenital sensorineural hearing loss cases (Francey et al, 2012;Markova et al, 2018;Shearer et al, 2014;Sloan-Heggen et al, 2016;Vona et al, 2015); however, this could be an underestimate given the variable STRC allele frequencies between ethnicities (Sloan-Heggen et al, 2016) and the ongoing appreciation of clinically relevant copy number variation at the STRC locus.…”
Section: To the Editormentioning
confidence: 99%